ON THE PROGNOSTICATION OF THE NEED IN SPECIALISTS IN THE SPHERE OF TRADE, HOSPITALITY INDUSTRY AND SERVICES - N. A. Aksenova (Russian Journal of Economics and Law)
The article suggests approaches to prognosticating the staff demand in the sphere of trade, hospitality industry and service; views the participants of the process and its main constituents; presents the technology of prognostication. The topicality of the issue is determined by the fact that the correct prognostication of the staff demands in economic sectors and social sphere, as well as the training of qualified needed specialists is one of the priority tasks of the successful functioning of a scientific-educational cluster.